(untitled) (Teaching and Learning Inquiry, 2021)
Although the Scholarship of Teaching and Learning (SoTL) claims to focus on student learning, some have argued that SoTL studies often adopt a narrow view of learning and focus more on teaching than on learning. In this paper, we explore whether teaching is the primary focus of recent articles published from 2013-2017 in three international, self-identified SoTL journals: Teaching and Learning Inquiry: The ISSOTL Journal (TLI), The International Journal for the Scholarship of Teaching and Learning (ijSOTL), and The Journal of the Scholarship of Teaching and Learning (JoSoTL). Based on our analysis of the 299 empirical articles, we argue that they portray SoTL as a field focused primarily on teacher activity rather than student learning, despite efforts to broaden its scope.